2017
DOI: 10.3389/fphar.2017.00575
|View full text |Cite
|
Sign up to set email alerts
|

The Immune System's Contribution to the Clinical Efficacy of EGFR Antagonist Treatment

Abstract: Epidermal Growth Factor Receptor (EGFR) antagonists were one of the first anti-cancer treatments developed targeting a Receptor Tyrosine Kinase. However, the underlying mode of action of how EGFR antagonist application can explain its clinical efficacy in different types of cancers remains largely unresolved. Numerous findings have suggested that a substantial portion of the effects attributed to EGFR antagonist treatment might not be based on direct influence on the tumor itself. Instead it may be based on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 45 publications
0
28
1
Order By: Relevance
“…Instead it may be based on indirect effects, potentially mediated via the immune system. EGFR antagonist treatment could be impacting tumor growth by blocking macrophage and regulatory CD4+ T cell function (29).…”
Section: Discussionmentioning
confidence: 99%
“…Instead it may be based on indirect effects, potentially mediated via the immune system. EGFR antagonist treatment could be impacting tumor growth by blocking macrophage and regulatory CD4+ T cell function (29).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have already reported that EGFR mutational status has been correlated to PD-L1 expression [43][44][45]46]. In particular, Chen et al in their work demonstrated that EGFR activation by EGF stimulation, exon-19 deletions, and L858R mutation could induce PD-L1 expression through p-ERK1/2/p-c-Jun [46].…”
Section: Discussionmentioning
confidence: 98%
“…In this scenario another strategy under investigation is the combination of immune modulators and anti-EGFR therapy in a RAS WT population, elucidating the notion that the immune system substantially contributes to the therapeutic effects of monoclonal antibodies (moAbs) [43], NCT02713373, NCT03442569).…”
Section: Discussionmentioning
confidence: 99%
“…More so, however intriguing the idea may be, it is pertinent to consider the associated challenges and drawbacks EGFR therapy might present. For instance, EGFR expression and function is crucial in all major immune cell types that include macrophages, T regs, dendritic cells, and so on and thus the administration of EGFR inhibitors or monoclonal antibodies to treat a particular pathology may render susceptibility to other pathologies and infections . It is known that Th2 responses are essential for controlling worm infections.…”
Section: Egfr‐directed Therapies For Persistent Infections: Future Pementioning
confidence: 89%